Filling in the Picture: Nineteenth-Century Museums in Spanish and Portuguese America - Podgorny, Irina (2016)
This special issue comprising articles on Argentina, Brazil, Colombia, Guatemala,and Mexico is devoted to museums established over the long nineteenth centuryin Spanish and Portuguese America. It features a variety of museums: from nationalto provincial, from monumental to one-room shows, from general to those devotedto a single subject, from lost to still existing. Awide variety of institutions in North,Central, and South America are examined in a century that witnessed the lastreforms of the Iberian empires, the impact of Napoleonic politics on the Atlanticworld, the long processes inaugurated by the wars of Revolution and Independence,the establishment of the Brazilian empire, and the convoluted configuration of the new Latin American Republics.